Comment 3779-1: Support for the proposed conservation of Petalodus Owen, 1840 by designation of a neotype for its type species Petalodus hastingsii Owen, 1840 - Lucas, Spencer G (Bulletin of Zoological Nomenclature, 2019)
http://dx.doi.org/10.21805/bzn.v76.a021